REPRODUCING NIGERIAN STATE TOWARDS REAL PRODUCTIVE INVESTMENT: RECONFIGURING SOCIAL SAFETY NETS ‘PALLIATIVE’ - BAMIDELE Samson Olukayode (Phd) (INJOSEDU: International Journal of Social and Education, 2026)
Globally, social safety nets have become one of the viable strategies put in place to alleviate poverty and help financial needs of vulnerable especially developing countries like Nigeria. The study examines the need for reconfiguring ‘Palliative’ towards real productive investment in Nigerian economy. This is predicated on the implementation of the programme that has been over politicized and corruption have undermined the lofty intention of the policy. Sampling technique was used to determine the specific local Government Areas to be drawn from each senatorial districts in Ekiti State. A total of 175 beneficiaries were selected out of 4500 beneficiaries using Yamane’s formula for determining sample size. The study used structure questionnaire technique. The data gathered were analysed using both descriptive and inferential statistics and presented in frequency distribution tables and percentages. While interview were conducted among adhoc staff of SSNs seconded from all LGAs in the State. The major findings of the study include that SSNs has improved school enrolment and attendance in Nigerian Primary Schools. It was found out that the programme did not touch the real poor in Nigeria because of corruption and that politicians explored the avenue for political patronage. The study recommends upward review of the stipends paying to beneficiaries monthly to be commensurate with the inflation in the country and there must be proper and adequate monitoring of the implementation of SSNs.